2016
DOI: 10.1016/j.psychsport.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Within- and between-person predictors of disordered eating attitudes among male and female dancers: Findings from the UK Centres for Advanced Training

Abstract: The authors wish to thank the Centres for Advanced Training for their fundamental role in this project and Trinity Laban's Dance Science team for support with data collections and entry. Additionally, we gratefully acknowledge the support of our funders: the Leverhulme Trust and the Department for Education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 57 publications
0
3
0
1
Order By: Relevance
“…The findings of the present study are thus somewhat unexpected since women generally exhibit a higher risk for developing an eating disorder, mostly due to expectations from the society and thin-idealization [37]. Nordin-Bates et al [38], in their longitudinal study, reported that the percentage of male and female dancers who scored above the cut-off in disordered eating attitudes changed between time points of data collection. Cross-sectional studies, like the present one, however, cannot compare time points due to obvious limitation and one-point data collection may not yield stable findings.…”
Section: Discussionmentioning
confidence: 58%
“…The findings of the present study are thus somewhat unexpected since women generally exhibit a higher risk for developing an eating disorder, mostly due to expectations from the society and thin-idealization [37]. Nordin-Bates et al [38], in their longitudinal study, reported that the percentage of male and female dancers who scored above the cut-off in disordered eating attitudes changed between time points of data collection. Cross-sectional studies, like the present one, however, cannot compare time points due to obvious limitation and one-point data collection may not yield stable findings.…”
Section: Discussionmentioning
confidence: 58%
“…By contrast, perceptions of task-involving motivational climates (focused on learning and personal development) are associated with higher selfesteem and lower weight-related pressure from peers and teachers (36). However, a more recent study indicates that an ego-involving climate in the dance environment could be more salient for male than for female dancers (37). Future research should further explore these context characteristics, which seem very important for the development of preventive interventions that include teachers and peers, in order to create and improve a climate of mastery (36).…”
Section: Dancersmentioning
confidence: 93%
“…However, several researchers have focused on understanding the psychological correlates for eating disorders in male athletes and dancers, which suggests that a model specifically developed for men, like the biopsychosocial model, is needed. For example, in a longitudinal study conducted in the United Kingdom, Nordin-Bates et al (2016) found that lower selfesteem predicted dysfunctional eating attitudes only in female dancers, and perceptions of high task or ego-involving climates predicted dysfunctional eating attitudes only in male dancers.…”
Section: Biopsychosocial Modelmentioning
confidence: 99%